Managerial skills in the international context: possible contributions of Brazilian's higher education programs in Business Management - e Sousa, Adriana de Faria; Valadão Junior, Vadir Machado (Organizações & Sociedade, 2013)
The objective of this study was to identify and analyze the managerial competenciescovered in menus disciplines of higher education courses of Business Management,that directly or indirectly contribute to the development of relevant skills to themanager who wants to take international assignments. It was selected a sampleof 24 institutions of higher education, based on the following criteria: (1) results ofNational Performance of Students (Enade) and on-site evaluation conducted by theMinistry of Education and Culture (MEC); (2) courses included in a program called."Pró Administração", connected to Universidade Federal de Uberlândia. There wasused classical content analysis, based on the descriptions of these courses, developedfrom parameters that were based on the results of survey among Brazilian managersworking abroad (Sousa et al., 2010) and studies of Echeveste and others (1999) andMcCall and Hollenbeck (2003). 1324 courses description have been evaluated, andin 622 (46.97% of the corpus) it was possible to identify adhesions to the proposedcompetencies. With greater frequency, were found: strategic vision, decision-makingability, capacity of correlation between events of importance to the company and abilityto deal with different cultures.